Frequency of Dyslipidemia among End-Stage Renal Disease Patients on Thrice Weekly Maintenance Hemodialysis - Fatima, Arooj; Anwar, Shahid; Awan, Abad-ur-Rehman; Ahmad, Sajad; Usman, Hafiz Tahir; Anwar, Zahid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Serum lipid abnormalities are strongly related to cardiovascular as well as all-cause mortality. The most common dyslipidemia among dialysis patients is low HDL followed by hypertriglyceridemia. Total cholesterol and LDL levels are normal. Dyslipidaemia in end-stage renal disease is multifactorial in addition to abnormalities in lipid metabolism, malnutrition, inflammation, low albumin, and inadequate hemodialysis also contribute to premature atherosclerosis. That’s why treatment of dyslipidemia in hemodialysis patients should be individualized. Objective: To determine the frequency of dyslipidemia among patients of end-stage renal disease on thrice-weekly hemodialysis. Study Design: Cross-sectional study Place and Duration of Study: Dialysis Unit, Department of Nephrology Sir Ganga Ram Hospital, Lahore from 1s9th March 2021, to 18th September 2021 Methodology: Seventy two patients having maintenance HD at our center were enrolled. The data included the patient’s name, age, gender, duration of maintenance hemodialysis, BMI, HTN, DM, IHD, and smoking status. Fasting lipid samples of patients were collected in serum vials and samples were analyzed in the major laboratory for any lipid abnormality. Results: Forty four (61.1%) patients have dyslipidemia among which 27 (61.4%) were males and 17 (38.6%) were females. The mean age was 47.5±11.5 years. The most common lipid abnormality in our patients was low HDL levels i.e., 56.8% followed by hypertriglyceridemia 6.9%. Total cholesterol and LDL levels are normal in 98% and 100% respectively. Conclusion: The frequency of dyslipidemia among patients of thrice-weekly maintenance hemodialysis is 61.1%. Low HDL is the most common lipid abnormality followed by hypertriglyceridemia 56.8% and 6.9% respectively.